Digital ethics from a gender perspective: Media literacy and the representation of deviant behaviour on social media - Furqany, Syahril; Sazali, Hasan; Khatibah, Khatibah; Ibrahim, Muhamad Shamsul bin; Almuntarizi, Almuntarizi; Azmy, Khairul (UIN Ar-Raniry Banda Aceh, 2026)
This study aims to analyse digital literacy among social media users from a gender perspective. The rapid development of communication technology, particularly the emergence of social media, has transformed human interaction from limited offline spaces into boundless online environments. On the one hand, this transformation enables individuals to connect with a wider audience and access vast amounts of information. On the other hand, it has also given rise to various issues, including violations of digital ethics, the spread of misinformation, and the presence of deviant behaviours on social media platforms. Strong digital literacy is essential to prevent the normalization of such deviations, particularly those related to gender issues in digital spaces, in order to foster a healthier online environment. Users are expected to critically evaluate misinformation, reject gender bias, and contribute to creating safe and ethical social media spaces. This study employs a descriptive qualitative method, examining social media phenomena and conducting interviews with 32 participants. The findings indicate that participants actively reject gender-related deviant content by reporting inappropriate accounts, maintaining their privacy, and critically assessing circulating content. Furthermore, this study recommends strengthening digital literacy through ethical awareness, mental health considerations, and balanced social media usage. Users are encouraged to engage with social media according to their needs, avoid excessive use, and report content containing elements of deviance, including gender-related deviations.